ARISTÓFANES, NUB. 329-334: EL POETA Y LOS INTELECTUALES - Rodríguez Alfageme, Ignacio (Myrtia, 2000)
In Nub . 329-334 Aristophanes enumerates the professionals who live without working. Between those we find physicians, sophists and fortune tellers. Our aim is the study of the composed word ἰατροτέχνης from the point of view of morphology and the context in order to determine what kind of physician is referred to by word.